Soil quality and microbial communities in subtropical slope lands under different agricultural management practices - Chen, Ching-Nuo; Liao, Chien-Sen; Tzou, Yu-Min; Lin, Yu-Te; Chang, Ed-Haun; Jien, Shih-Hao (Frontiers in Microbiology, 2024)
Land degradation is a major threat to ecosystem. Long-term conventional farming practices can lead to severe soil degradation and a decline in crop productivity, which are challenging for both local and global communities. This study was conducted to clarify the responses on soil physicochemical properties and microbial communities to changes in farming practices. Slope land orchards under three agricultural management practices-conventional farming (CF), organic farming (OF), and ecofriendly farming (EFF)-were included in this study. We found that soil carbon stock increased by 3.6 and 5.1 times in surface soils (0-30 cm) under EFF and OF treatments, respectively. EFF and OF significantly increased the contents of total nitrogen by 0.33-0.46 g/kg, ammonia-N by 3.0-7.3 g/kg, and microbial biomass carbon by 0.56-1.04 g/kg but reduced those of pH by 0.6 units at least, and available phosphorous by 104-114 mg/kg. The application of phosphorous-containing herbicides and chemical fertilizers might increase the contents of phosphorous and nitrate in CF soil. High abundances of Acidobacteria and Actinobacteria were observed in EFF and OF soils, likely because of phosphorous deficiency in these soils. The abundance of fungi in OF soil indicated that plants' demand for available soil phosphorous induced the fungus-mediated mineralization of organic phosphorous. High abundances of Gammaproteobacteria, Planctomycetes, Firmicutes, and Nitrospirae were observed in CF soil, possibly because of the regular use of herbicides containing phosphorous and chemical fertilizers containing high total nitrogen contents.